Blunt renal trauma: biomechanics and origination of renal lesions - Bschleipfer, Thomas; Kallieris, Dimitrios; Hauck, E. W.; Weidner, W.; Pust, R. A. (European urology, 2002)
Computer-assisted simulation of trauma is supposed to improve protective systems in traffic and risky leisure activities. In case of blunt renal injury biomechanical data being concerned with kidneys as a whole are extremely sparse. To enable three-dimensional simulations this study should supply important data of the renal biomechanics and elucidate the relationship between force distribution and origination of renal lesions.
Gesehen am 21.04.2021